Law Enforcement Against the Crime of Sexual Exploitation of Children in the Legal Systems of Indonesia and Malaysia - Witasya Aurelia Sulaeman; Beniharmoni Harefa; Handar Subhandi Bakhtiar (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
Child sexual exploitation is a severe violation of human rights that demands a firm and multidimensional legal response. This study aims to identify the underlying causes of child sexual exploitation and to analyze and compare law enforcement practices against such crimes within the legal systems of Indonesia and Malaysia. The research employs a normative juridical method with a comparative law approach. The findings reveal that the contributing factors in both countries include weak legal enforcement, socio-economic vulnerability, misuse of digital technology, and prevailing cultural norms. In terms of punishment, Indonesia has introduced chemical castration as an additional sanction under Government Regulation No. 70 of 2020, while Malaysia imposes imprisonment and caning based on the Penal Code and the Child Act 2001. Despite having comprehensive legal frameworks, Indonesia continues to face challenges in implementation, such as inadequate law enforcement sensitivity and insufficient psychosocial support for victims. The comparative analysis indicates that legal effectiveness relies not only on statutory provisions but also on institutional commitment to uphold justice and child protection.